Strengthening Financial Reporting Regimes and the Accountancy Profession and Practices in Selected Caribbean Countries - World Bank Group (World Bank, Washington, DC, 2015)
The main objectives of this report are to: (a) provide a synthesized analysis of financial reporting and auditing standards and practices across the countries in which the Institute of Chartered Accountants of the Caribbean (ICAC) is active and (b) provide a basis for recommendations to ICAC and respective national institutes for a regional strategy to enhance the accounting profession and the accounting and auditing practices in the public and private sectors. This report’s focus on reforms and identification of areas and means to strengthen the accounting profession have at their root the conviction that systemic enhancements to the standards and practices of the profession can materially improve the lives of the region’s populace, particularly its less prosperous citizens, through greater transparency, strengthened economic growth and its attendant employment and tax revenue prospects, and greater access to financing for and formalization of the region’s dominant sector-micro, small, and medium-sized enterprises (MSMEs). The report finds that a constraint limiting both investment across the region, particularly to MSMEs that characterize the respective national economies, and the efficient use of public resources is the accounting and auditing practices and the financial reporting regimes that prevail in both the public and private sectors. This finding emerges from: (i) a review of Reports on the Observance of Standards and Codes for Accounting and Auditing (ROSC AA) conducted by the World Bank for Jamaica, Trinidad and Tobago, Suriname, and the countries of the Organisation of Eastern Caribbean States, and (ii) Bank missions to those countries updating the ROSC findings as well as missions to countries that have not yet had ROSC AA reviews (during which the Bank team met the national accountancy body, regulators of entities that fall within the financial reporting chain, supreme audit institutions, central banks, and so forth so as to secure information that would typically be found in formal ROSC AA reports).